Water Balance Dynamics during Ten Years of Ecological Development at Chicken Creek Catchment. Issue 11 (10th November 2017) - Schaaf, Wolfgang; Pohle, Ina; Maurer, Thomas; Gerwin, Werner; Hinz, Christoph; Badorreck, Annika
Abstract : Core Ideas: Water balance was calculated for the constructed catchment Chicken Creek. Influence of abiotic and biotic factors feedback mechanisms on the hydrology was determined. Different phases were derived during the development of the ecohydrological system. Difficulties in quantitatively closing the water balance of catchments arise when upscaling point measurements and from insufficient knowledge of the physical boundaries, inner structure, and storage volumes of natural catchments. In addition, there is a strong need for generalizing the relationship between catchment characteristics and hydrological response. Therefore, experimental catchments with well‐known boundaries and conditions could contribute valuable data to hydrological and critical zone research. One of the most well‐established and largest constructed catchments is the Chicken Creek catchment (6 ha including a pond, Brandenburg, Germany) representing an initial ecosystem undergoing highly dynamic ecological development starting from clearly defined starting conditions. Directly after completion of the construction, extensive monitoring equipment was installed to track the ecosystem development and to capture the spatiotemporal variability of meteorological, hydrological, ecological, and soil conditions and vegetation succession. In this study, we focused on the water balance dynamics of the Chicken Creek catchment for the period 2005 to 2015 as influenced by ecological development. Water storage in the catchment was calculated from a three‐dimensional model of groundwater volumes, soil moisture measurements, and water level recordings of the pond. The catchment water balance equation was resolved for evapotranspiration, the only part that was not measured directly. Time series of meteorological, hydrological, and ecological data for 10 yr enabled us to characterize the transient development of the catchment and to evaluate the effect of different feedback mechanisms on catchment hydrology.